Cell-specific rates of sulfate reduction and fermentation in the sub-seafloor biosphere - Jaussi, Marion; Jørgensen, Bo Barker; Kjeldsen, Kasper U.; Lomstein, Bente A.; Pearce, Christof; Seidenkantz, Marit-Solveig; Røy, Hans (Frontiers in Microbiology, 2023)
Microorganisms in subsurface sediments live from recalcitrant organic matter deposited thousands or millions of years ago. Their catabolic activities are low, but the deep biosphere is of global importance due to its volume. The stability of deeply buried sediments provides a natural laboratory where prokaryotic communities that live in steady state with their environments can be studied over long time scales. We tested if a balance is established between the flow of energy, the microbial community size, and the basal power requirement needed to maintain cells in sediments buried meters below the sea floor. We measured rates of carbon oxidation by sulfate reduction and counted the microbial cells throughout ten carefully selected sediment cores with ages from years to millions of years. The rates of carbon oxidation were converted to power (J s -1 i.e., Watt) using the Gibbs free energy of the anaerobic oxidation of complex organic carbon. We separated energy dissipation by fermentation from sulfate reduction. Similarly, we separated the community into sulfate reducers and non-sulfate reducers based on the dsrB gene, so that sulfate reduction could be related to sulfate reducers. We found that the per-cell sulfate reduction rate was stable near 10 -2 fmol C cell -1 day -1 right below the zone of bioturbation and did not decrease with increasing depth and sediment age. The corresponding power dissipation rate was 10 -17 W sulfate-reducing cell -1 . The cell-specific power dissipation of sulfate reducers in old sediments was similar to the slowest growing anaerobic cultures. The energy from mineralization of organic matter that was not dissipated by sulfate reduction was distributed evenly to all cells that did not possess the dsrB gene, i.e., cells operationally defined as fermenting. In contrast to sulfate reducers, the fermenting cells had decreasing catabolism as the sediment aged. A vast difference in power requirement between fermenters and sulfate reducers caused the microbial community in old sediments to consist of a minute fraction of sulfate reducers and a vast majority of fermenters.